Ukraine : Technical Assistance Report-Regulation of Market Abuse and Issuer Disclosure Requirements. (IMF Staff Country Reports; Country Report ;, 2016)
This Technical Assistance report examines regulation of market abuse and issuer disclosure requirements in Ukraine. The Ukrainian regulatory framework for market abuse and issuer disclosure requirements has significant gaps, whose impact is compounded by the National Securities and Stock Market Commission's (NSSMC) lack of sufficient supervisory, investigative, and enforcement powers. This has contributed to overall lack of transparency and widespread misconduct in the market, including through issuance and trading of 'fictitious' securities. To address the current challenges, the Ukrainian legislation needs to be aligned with the international standards to provide the NSSMC with sufficient means to require enhanced disclosures and combat market abuse.